2021
DOI: 10.1002/ece3.7347
|View full text |Cite
|
Sign up to set email alerts
|

The importance of environmental conditions in maintaining lineage identity in Epithelantha (Cactaceae)

Abstract: The study of diversification processes in megadiverse groups has been strengthened by the inclusion of bioclimatic and other environmental information (Jones et al., 2014;Nevado et al., 2018). The Cacteae tribe has nearly 384 species and a high number of endemisms (Vázquez-Sánchez et al., 2013). This tribe diversified due to climate changes; however, there are no studies focusing on which specific biotic or abiotic factors contributed to its diversification and infer the speciation process (Hernández-Hernández… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Supertextae, four clades are formed, two of which have distinctive climatic and topographic characteristics: Clade S1 (M. haageana, M. albialanta, M. dixanthocentron and M. supertexta), with species that are distributed in warm zones mainly at altitudes ranging from 447 to 2318 meters in thorn and tropical deciduous forests; and Clade S2 (M. haageana, M. albilanata and M. flavicentra), with species that are distributed in temperate zones at altitudes that range mainly from 1285 to 2518 meters in pine-oak forests. The environmental, geological and topographic differences between closely related species produced during climatic changes suggest differential selection pressures and local adaptation, which could have driven the speciation process (Mastretta-Yanes et al 2015;Aquino et al 2021), as has been suggested for Mammillaria pectinifera (Cornejo-Romero et al 2014), Cephalocereus columna-trajani (Cornejo-Romero et al 2017) and the genus Epithelantha (Aquino et al 2021). Mammillaria haageana and M. albilanata represent a complex that extends widely in southern Mexico.…”
Section: Discussionmentioning
confidence: 88%
“…Supertextae, four clades are formed, two of which have distinctive climatic and topographic characteristics: Clade S1 (M. haageana, M. albialanta, M. dixanthocentron and M. supertexta), with species that are distributed in warm zones mainly at altitudes ranging from 447 to 2318 meters in thorn and tropical deciduous forests; and Clade S2 (M. haageana, M. albilanata and M. flavicentra), with species that are distributed in temperate zones at altitudes that range mainly from 1285 to 2518 meters in pine-oak forests. The environmental, geological and topographic differences between closely related species produced during climatic changes suggest differential selection pressures and local adaptation, which could have driven the speciation process (Mastretta-Yanes et al 2015;Aquino et al 2021), as has been suggested for Mammillaria pectinifera (Cornejo-Romero et al 2014), Cephalocereus columna-trajani (Cornejo-Romero et al 2017) and the genus Epithelantha (Aquino et al 2021). Mammillaria haageana and M. albilanata represent a complex that extends widely in southern Mexico.…”
Section: Discussionmentioning
confidence: 88%
“…This epoch was marked by global climatic changes (Amidon et al, 2016, 2017) and orogenic activity in the Neotropics (París, 2006). Climatic and geomorphological changes might have played an important role in the biome transition and diversification of Cactaceae in xeric areas of South America (Aquino et al, 2021; Bonatelli et al, 2014; Franco, Jojima, et al, 2017; Lavor et al, 2019; Silva, Ribas, et al, 2018). Indeed, the global aridification during the Miocene/Pliocene is highlighted as a driver of diversification for succulent species (Arakaki et al, 2011; Gutiérrez‐Ortega et al, 2018; Hebert et al, 2016; Horn et al, 2014; Hurbath et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that other soil characteristics, such as pH and salinity, might be important predictors of diversity. Recently, Aquino et al (2021) used a detailed Mexican soil database to highlight the relevance of soil pH in explaining patterns of distribution of the cactus genus Epithelantha .…”
Section: Discussionmentioning
confidence: 99%